(untitled) (Research, Society and Development, 2022)
The objective of this work was to apply technologies to obtain energy concentrate (maltodextrin) and protein concentrate (CPA) from broken rice. Initially, the broken rice was ground and subjected to pre-gelatinization, where 100 g of the raw material was suspended in water and heated to 90°C under constant agitation (30 minutes). In it, increasing volumes of amylase (250, 350, 450, 550, 1000 and 2000 µL) were tested, aiming at greater interconversion of starch into maltodextrin. After the addition, the reaction continued for another 30 minutes and then it was filtered through a 150 micron mesh sieve. The solid fraction retained on the sieve was weighed and dried in an air circulation oven (50ºC/24 hours), obtaining the rice protein concentrate. To obtain the maltodextrin, the liquid fraction was dried in a spray dryer (120ºC and flow rate of 1L/hour). In the products obtained, crude protein and yield were determined, in addition to economic viability calculation. The results showed that the use of 250 µL of amylase is recommended, as it results in an adequate yield (65.02%) of maltodextrin and acceptable levels of crude protein (21.64%). The technique used is low cost, making it possible to obtain two innovative products that can be used in nutritional strategies for different species and stages of animal development, while strengthening the integration and economic sustainability of rice production chains.